Role of ultrasound and color Doppler in the evaluation of acute scrotal pain - Salahuddin, Gazi; Nayeem, SM Zulker; Hossain, Syed Mozammel; Parvin, Sadika; Hossain, Md Monoar (Bangladesh Medical Journal Khulna, 2018)
Background: Traditionally acute scrotal pain is evaluated by gray scale ultrasound, which dissipated only the morphological changes of the lesion. But pattern of vascularity either normal, increased or absent of affected structure help to definitive diagnosis of the lesion and help to proceed the type of management either medical therapy or surgical treatment. Objectives: To determine the relative importance of color Doppler in the evaluation of acute scrotal pain by ultrasound. Methods: From June 2013 to June 2017 a total 150 patients with acute scrotal pain were selected. A thorough history taking and physical examination were done. Then patient were scanned with gray scale ultrasound followed by color Doppler study. Color Doppler diagnosis is compared with gray scale diagnosis. Results: In gray scale ultrasonography among the 150 cases, 54% were diagnosed as epididymitis, 16.66% were epididymo-orchitis and 16% patient diagnosed as normal. But in combined gray scale and colour Doppler study 58% were diagnosed as epididymitis, 22% were epididymo-orchitis and 6% of patient diagnosed as normal. In gray scale 10% patient were diagnosed as normal but become epididymitis and epididymo-orchitis in colour Doppler. Four percent were diagnosed as epididymitis in gay scale but became epididymo-orchitis in colour Doppler. Four percent patient was diagnosed as epididymitis orchitis but became testicular torsion in Doppler study. Total 14.66% of gray scale diagnosis became another diagnosis in the Doppler study. Conclusion: Combined gray scale and color Doppler study is superior than gray scale ultrasound in differentiating various cause of acute scrotal pain. Bang Med J (Khulna) 2017; 50 : 26-30